Mapping Mountain Landforms and Its Dynamics: Study Cases in Tropical Environments - Campos, Néstor (2022)
High mountain areas are critical for water security and natural hazard dynamics, as well as glacier and ecosystem conservation in a warming world. We present a brief account of the methodological steps for geomorphological mapping in mountain areas, including the required scale, the legends, technology, and software. We analyze the best imagery sources and their combination with fieldwork and geographical information systems (GIS), in performing accurate cartography. In addition, we present two case studies in which we apply several methods described previously. Firstly, we carried out a classical and digital geomorphological mapping of Cerro Chirripó (Talamanca Range). Secondly, we studied the Reserva Biológica Alberto Manuel Brenes (Central Volcanic Range), where we used UAVs to map high-resolution fluvial geomorphology. This methodological framework is suitable for future geomorphological surveys in mountain areas worldwide. Moreover, the case studies can give ideas on the application of these approaches to different mountainous environments.